2013
DOI: 10.1002/gcc.22040
|View full text |Cite
|
Sign up to set email alerts
|

Histone methyltransferase Suv39h1 deficiency prevents Myc‐induced chromosomal instability in murine myeloid leukemias

Abstract: Suv39h1 mediates heterochromatin formation in pericentric and telomeric regions by trimethylation of lysine 9 of histone 3 (H3K9me3). Yet, its role in the induction of chromosomal instability is poorly understood. We established a leukemia model by retrovirally expressing Myc in wild-type and histone methyltransferase Suv39h1-deficient hematopoietic cells and characterized the resulting leukemias for chromosomal instability. All mice that received cells overexpressing Myc developed myeloid leukemia with a medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Loss of another HMT, SUV39H1, in MYC-driven myeloid leukemia prevented chromosomal instability in mouse models, indicating that it may be a potentially useful therapeutic target [175]. NV10, a small molecule inhibitor of SUV39H1, exhibited anti-cancer activity in vivo and in vitro in several cancers [176].…”
Section: Therapeutic Strategies: Targeting Epigenetic Mechanisms Imentioning
confidence: 99%
“…Loss of another HMT, SUV39H1, in MYC-driven myeloid leukemia prevented chromosomal instability in mouse models, indicating that it may be a potentially useful therapeutic target [175]. NV10, a small molecule inhibitor of SUV39H1, exhibited anti-cancer activity in vivo and in vitro in several cancers [176].…”
Section: Therapeutic Strategies: Targeting Epigenetic Mechanisms Imentioning
confidence: 99%
“…Study of a leukemia mouse model revealed histone methyltransferase Suv39h1-deficient hematopoietic cells that showed less critical short telomeres and upregulated genes involved in ALT mechanism [133]. Suv39h1 mediates heterochromatin formation in pericentric and telomeric regions by trimethylation of lysine 9 of histone 3 (H3K9me3).…”
Section: Epigenetic Regulation Of Tmmsmentioning
confidence: 99%
“…As expected, clonal chromosomal aberrations induced by c-Myc overexpression were found in c-Myc/ wt leukemias of about one-third of primary recipients and in more than 80% of secondary recipients [79]. Notably, leukemias that arose in c-Myc/Suv39h1 -null mice were chromosomally stable, demonstrating that reduced H3K9 trimethylation due to lack of Suv39h1 rather protects leukemic cells from the development of CIN.…”
Section: Epigeneticsmentioning
confidence: 57%